Plant community formation and species distribution pattern in relation to environmental variables in Endiras Natural Forest, northwest Ethiopia - Getinet Masresha; Worku Misganaw; Endale Adamu (All Life)
The study was conducted in Endiras Forest, northwest Ethiopia, to evaluate the effects of environmental variables on the patterns of plant community formation. A systematic random sampling technique was used to collect vegetation data from 56 (20 m × 20 m) plots laid at 100 m intervals on ten transects. In each plot, the species encountered and its percent cover abundance were recorded, which was later transformed into a modified Braun-Blanquet scale. The composite soil samples collected from 15 cm × 15 cm subplots were examined for 13 soil parameters. Communities were determined using cluster analysis. The Shannon-Wiener index was employed to quantify species diversity. The relationships between species and environmental variables were evaluated using canonical correspondence analysis (CCA). Seventy-three woody plant species, distributed in 40 families, were documented. Fabaceae was found to be the most species-rich family (20.55%). Five communities were generated from the cluster analyses that vary in diversity. Nine environmental variables were found to be significant in determining patterns of community formation (P < 0.05). Organic matter, pH, and altitude, highly correlated with CCA axis 1, largely shaped the community formation patterns. Various patterns of community formation demonstrate the need to design different conservation measures.